Accuracy and precision in camera-based fluorescence correlation spectroscopy measurements - Sankaran, Jagadish (2013)
Imaging fluorescence correlation spectroscopy (FCS) performed using array detectors has been successfully used to quantify the number, mobility, and organization of biomolecules in cells and organisms. However, there have not been any systematic studies on the errors in these estimates that are introduced due to instrumental and experimental factors. State-of-the-art array detectors are still restricted in the number of frames that can be recorded per unit time, sensitivity and noise characteristics, and the total number of frames that can be realistically recorded. These limitations place constraints on the time resolution, the signal-to-noise ratio, and the total measurement time, respectively. This work addresses these problems by using a combination of simulations and experiments on lipid bilayers to provide characteristic performance parameters and guidelines that govern accuracy and precision of diffusion coefficient and concentration measurements in camera-based FCS. We then proceed to demonstrate the effects of these parameters on the capability of camera-based FCS to determine membrane heterogeneity via the FCS diffusion laws, showing that there is a lower length scale limit beyond which membrane organization cannot be detected and which can be overcome by choosing suitable experimental parameters. On the basis of these results, we provide guidelines for an efficient experimental design for camera-based FCS to extract information on mobility, concentration, and heterogeneity.